2022
DOI: 10.1093/hr/uhac164
|View full text |Cite
|
Sign up to set email alerts
|

The C4 protein of tomato yellow leaf curl Sardinia virus primes drought tolerance in tomato through morphological adjustments

Abstract: Viruses can interfere with the ability of plants to overcome abiotic stresses, indicating the existence of common molecular networks that regulate stress responses. A begomovirus causing the tomato yellow leaf curl disease was recently shown to enhance heat tolerance in tomato and drought tolerance in tomato and Nicotiana benthamiana and experimental evidence suggested that the virus-encoded protein C4 is the main trigger of drought responses. However, the physiological and molecular events underlying C4-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…These compounds functionally decrease the cell water potential, consequently lowering the freezing point of cellular fluids and bolstering the plant’s resistance to cold stress. The prominence of starch, soluble sugars, soluble proteins, and free proline as pivotal osmolytes in this context is well documented [ 27 ]. Starch, for instance, appears to serve a dual role: firstly, as an energy reservoir to sustain the plant during dormancy, and secondly, upon its degradation, as a source of soluble sugars.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds functionally decrease the cell water potential, consequently lowering the freezing point of cellular fluids and bolstering the plant’s resistance to cold stress. The prominence of starch, soluble sugars, soluble proteins, and free proline as pivotal osmolytes in this context is well documented [ 27 ]. Starch, for instance, appears to serve a dual role: firstly, as an energy reservoir to sustain the plant during dormancy, and secondly, upon its degradation, as a source of soluble sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts expression levels were normalized to the geometric mean of the ubiquitin (VvUBI) and actin (VvACT) transcripts and calculated with the 2 −∆Ct method using CFX Maestro software v. 2.3 (Bio-Rad Laboratories, Inc.). Oligonucleotide sequences are listed in Table S1 [25,26,34].…”
Section: Rna Isolation and Rt-qpcr Analysis Of Target Genes Involved ...mentioning
confidence: 99%
“…Until now, no study has investigated the gene expression patterns of VvEPFL9 and other putative genes associated with stomagenesis in grapevine plants under varying water availability. Furthermore, it is unclear whether immature leaves possess the ability to detect water deficit both at the biochemical level (such as responses mediated by the abscisic acid-ABA hormone) and at the molecular level, by activating gene pathways in response to drought (such as ABA-responsive genes like dehydrin (DH), a well-recognized marker of drought in plants, including grapevines) [24][25][26]. These data could enhance our understanding of the molecular pathways involved in stomatal development under drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wilting in Begomovirus (DNA virus) Tomato yellow leaf curl Sardinia virus (TYLCSV) infected tomato was slower and post-dehydration recovery was faster compared to healthy plants (Sacco Botto et al 2023 ). In another study, C4 protein of TYLCSV has been found to prime drought tolerance in tomato through morphological adjustments, indicating the potential of viral proteins in enhancing plant resilience to drought stress (Pagliarani et al 2022 ). Moreover, C4 protein of Begomovirus Tomato yellow leaf curl virus (TYLCV) also has been shown to provide tolerance to drought in tomato and N. benthamiana (Corrales-Gutierrez et al 2020 ).…”
Section: Introductionmentioning
confidence: 97%